(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this journey, we are going to explore the separation axioms in greater detail. Separation axioms are one among the most common, important and interesting concepts in Topology. They can be used to define more restricted classes of topological spaces.